A Simplified Method to Measure Choroidal Thickness Using Adaptive Compensation in Enhanced Depth Imaging Optical Coherence Tomography - Gupta, Preeti; Sidhartha, Elizabeth; Girard, Michael J. A.; Mari, Jean Martial; Wong, Tien-Yin; Cheng, Ching-Yu (PloS one, 2014)
To evaluate a simplified method to measure choroidal thickness (CT) using commercially available enhanced depth imaging (EDI) spectral domain optical coherence tomography (SD-OCT). We measured CT in 31 subjects without ocular diseases using Spectralis EDI SD-OCT. The choroid-scleral interface of the acquired images was first enhanced using a post-processing compensation algorithm. The enhanced images were then analysed using Photoshop. Two graders independently graded the images to assess inter-grader reliability. One grader re-graded the images after 2 weeks to determine intra-grader reliability. Statistical analysis was performed using intra-class correlation coefficient (ICC) and Bland-Altman plot analyses. Using adaptive compensation both the intra-grader reliability (ICC: 0.95 to 0.97) and inter-grader reliability (ICC: 0.93 to 0.97) were perfect for all five locations of CT. However, with the conventional technique of manual CT measurements using built-in callipers provided with the Heidelberg explorer software, the intra- (ICC: 0.87 to 0.94) and inter-grader reliability (ICC: 0.90 to 0.93) for all the measured locations is lower. Using adaptive compensation, the mean differences (95% limits of agreement) for intra- and inter-grader sub-foveal CT measurements were -1.3 (-3.33 to 30.8) µm and -1.2 (-36.6 to 34.2) µm, respectively. The measurement of CT obtained from EDI SD-OCT using our simplified method was highly reliable and efficient. Our method is an easy and practical approach to improve the quality of choroidal images and the precision of CT measurement.